Spectroscopic and Colorimetric Determination of Meloxicam, Lornoxicam, Tenoxicam in Drugs: Spectroscopic and Colorimetric Determination of Meloxicam, Lornoxicam, Tenoxicam in Drugs - Chaplenko, A. A. (International Journal of Pharmaceutical & Biological Archive, 2018)
New approach to spectrophotometric and colorimetric determination of meloxicam, lornoxicam, tenoxicam in drugs using 7-chloro-4-nitrobenz-2-oxa-1,3-diazole (NBD chloride) is developed. The techniques are based on alkaline hydrolyses of oxicams with NBD chloride and the subsequent spectrophotometric and colorimetric determination of the colored products of reaction. The linearity range of calibration dependence is 1-10 mg/ml for lornoxicam and tenoxicam, 0.5-5 mg/ml for meloxicam. The advantages of developed methods are rapidity and cost-efficiency. This approach can be used for screening control of drug quality.